Benefits of rehabilitation in postoperative lumbar spine surgery and its main intervention strategies: systematic review (Research, Society and Development, 2022)
Low back pain (LBP) is common and has come to be considered a global health problem, due to the disability it generates. Surgery should be proposed when conservative treatment fails or neurological symptoms progress. Objective: The objective of this research is to describe the main strategies in the rehabilitation of patients submitted to lumbar spine surgery, with or without arthrodesis, for herniated discs, spondylolisthesis or stenosis. In addition, to evaluate the results of these interventions in the parameters pain, function and disability. The review was based on articles indexed in the PubMed and Cochrane Library databases, using the keywords: Postoperative; Physical Therapy; Lumbar Spine. Result: As well as their respective keywords in English: Postoperative; Physiotherapy; lumbar spine. A total of 407 articles were found. After applying the inclusion and exclusion criteria, filters and then making the eligibility by reading the abstracts, the total number of articles included in the study was 8. Conclusion: It is concluded, therefore, that postoperative rehabilitation of lumbar spine surgery is still uncertain. Active rehabilitation through exercises is better than doing nothing, but there is doubt as to whether the type of activity should be specific or general activities. The start of rehabilitation varies from immediately, the day after surgery, to 3 months after surgery. Likewise the length of intervention can last up to 12 months.